2019
DOI: 10.3390/su11061520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N Addition Frequency and Quantity on Hydrocotyle vulgaris Growth and Greenhouse Gas Emissions from Wetland Microcosms

Abstract: (1) Background: Increased attention has been paid to atmospheric nitrogen (N) deposition caused by human activities. N deposition quantity has seriously affected plant productivity and greenhouse gas emissions in wetlands, but the effects of N deposition frequency remain unclear. (2) Methods: We assembled microcosms, which contained vegetative individuals (ramets) of Hydrocotyle vulgaris and soil and subjected them to three frequencies (N addition 1, 2, and 14 times during the experimental period) crossed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Jia et al found that N 2 O emissions increased by 134% under high N treatment in a study of coastal wetlands [31]. Similarly, N levels significantly contribute to N 2 O emissions in the urban wetland in Zhejiang Province, China [32]. Song et al concluded that N addition increased N 2 O emissions by 54.53% in permafrost peatland [33].…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al found that N 2 O emissions increased by 134% under high N treatment in a study of coastal wetlands [31]. Similarly, N levels significantly contribute to N 2 O emissions in the urban wetland in Zhejiang Province, China [32]. Song et al concluded that N addition increased N 2 O emissions by 54.53% in permafrost peatland [33].…”
Section: Discussionmentioning
confidence: 99%
“…The species can reproduce both sexually and asexually; therefore, it has spread extensively to some wetlands in China, such as Hangzhou Bay [39]. This species is now considered invasive in China [40,43,44].…”
Section: Plant Materialsmentioning
confidence: 99%
“…P and T represent the air pressure (kPa) and temperature (K) in situ. H represents the height of the gas-sampling box (m) [43,53]. The cumulative emission fluxes of the greenhouse gases were calculated by the following formula:…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%
“…SOC mainly is produced from root exudates and the decomposition of litter and crop residues [3][4][5]. The progress is susceptible to cultivation practices, which adjust soil environments, i.e., the soil pH, soil water content, enzyme activities, and soil microbes [6][7][8][9]. Kuzyakov and Domanski (2000) noted that wheat and barley transport about 30% of the assimilated C production into soil [10].…”
Section: Introductionmentioning
confidence: 99%